2022
DOI: 10.3390/ma15207374
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite Coating on Ti-6Al-7Nb Alloy by Plasma Electrolytic Oxidation in Salt-Based Electrolyte

Abstract: Titanium alloys have good biocompatibility and good mechanical properties, making them particularly suitable for dental and orthopedic implants. Improving their osseointegration with human bones is one of the most essential tasks. This can be achieved by developing hydroxyapatite (HA) on the treating surface using the plasma electrolytic oxidation (PEO) method in molten salt. In this study, a coating of titanium oxide-containing HA nanoparticles was formed on Ti-6Al-7Nb alloy by PEO in molten salt. Then, sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…It was in line with other studies, where the formation of abundant nano- and micro-pores was observed for PEO in electrolytes with Ca and P ions and other additives, particularly Mn and Si . Moreover, the process of formation of a bioactive coating consisting of titanium oxides and hydroxyapatites in Ti alloys by PEO was recently shown to be effective in molten salts as bath electrolytes . Interestingly, PEO processing was also applied to control the biodegradation rate and biocompatibility of magnesium implants in experiments in rabbits in vivo .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It was in line with other studies, where the formation of abundant nano- and micro-pores was observed for PEO in electrolytes with Ca and P ions and other additives, particularly Mn and Si . Moreover, the process of formation of a bioactive coating consisting of titanium oxides and hydroxyapatites in Ti alloys by PEO was recently shown to be effective in molten salts as bath electrolytes . Interestingly, PEO processing was also applied to control the biodegradation rate and biocompatibility of magnesium implants in experiments in rabbits in vivo .…”
Section: Discussionsupporting
confidence: 88%
“…38 Moreover, the process of formation of a bioactive coating consisting of titanium oxides and hydroxyapatites in Ti alloys by PEO was recently shown to be effective in molten salts as bath electrolytes. 39 Interestingly, PEO processing was also applied to control the biodegradation rate and biocompatibility of magnesium implants in experiments in rabbits in vivo. 40 Our report demonstrated the capacity of the chelating agent to initiate deposition of Ca−P complexes as substrates for the PEO processing, which resulted in surface layers with advanced bioactive parameters.…”
Section: Discussionmentioning
confidence: 99%
“…When a capacitor is omitted from the circuit, no current can flow because, when the capacitor is charged, the current will not pass, and the circuit will be cut off. The dense oxide layer on the surface of the titanium also has this effect and, such as a capacitor after being fully charge, disrupts the electrical circuit by reducing the corrosion rate [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Based on the EIS diagrams and the obtained data, it can be concluded that the corrosion resistance of the sample with plasma electrolytic oxidation coating is better than that of the uncoated sample.…”
Section: Resultsmentioning
confidence: 99%
“…The process combines electrochemical oxidation of metal surfaces with a high-voltage (up to 500 V, often AC) spark treatment carried out in aqueous electrolytic baths. However, in 2022, the first paper on the PEO process carried out in a molten salt electrolyte (the authors used molten nitrates) was published [578]. In addition, ultrasound might be applied during the MAO process (called UMAO = ultrasound MAO) [579]; there is also a more complicated hybrid UMAOH (=UMAO hybrid) process, which consists of two stages: UMAO with ultrasound treatment for 8 min and subsequent MAO without ultrasound for 2 min.…”
Section: Micro-arc Oxidation (Mao) Techniquementioning
confidence: 99%